Uji Parameter Non Spesifik dan Aktivitas Antibakteri Ekstrak Metanol dari Umbi Tanaman Dahlia (Dahlia variabilis) - Haryani, Yuli; Muthmainah, Siti; Sikumbang, Saryono (Jurnal Penelitian Farmasi Indonesia, 2013)
Dahlia variabilis is one of plant that commonly growing in highland hills in Indonesia. The preliminary screening on secondary metabolitesshowed that the presence of flavonoids, phenolics and saponin in methanol extract of this plant’s tuber. Its methanol extract was subjectedto the evaluation of non-specific parameter of extract standardization as well as antimicrobial assay using disc diffusion method againstEscherichia coli and Staphylococcus aureus. The result revealed that the methanol extract contained 25.48±1.63% of water content,4.06±0.15% of ash content, and there was no heavy metal contamination detected. Antibacterial activity assay of three differenceconcentrations of the extract (10; 8 and 2%) demonstrated that extract with 10% of concentration gave the strongest activity against twotested bacterium with diameter of inhibition of 8.67±0.57 and 8.33±0.28 mm against Escherichia coli and Staphylococcus aureus, respectively.